Urgency of the Presidential Institution: Strengthening Presidentialism or Perfecting the State System in Indonesia - Muhammad Mutawalli,; Georges Olemanu Lohalo,; Imsirovic, Mirela (Al-Daulah : Jurnal Hukum Pidana dan Ketatanegaraan, 2024)
Research Objective: This study emphasizes the importance of strengthening Indonesia's presidential institution through the advancement of presidentialism and the refinement of its constitutional framework, while also exploring the historical development of presidential power within the country's political dynamics. Research Method: The research employed a qualitative approach, conducting a systematic analysis of existing literature, legal frameworks, and political practices. This analysis assessed the evolution of the presidential institution and its current operational context within Indonesia's constitutional system and democratic governance framework. Results: Identifying correlations between presidential authority and governance effectiveness as the institution has adapted to changing political landscapes and constitutional amendments. The study uncovers patterns of institutional evolution across various presidential administrations. Findings and Implications: The presidential institution is essential for effective governance, particularly in enhancing decision-making processes and ensuring political stability. The research demonstrates that a robust presidential system significantly improves policy implementation and government coherence, while also underscoring the need for constitutional improvements to establish appropriate inter-institutional checks and balances. Conclusion: A strong presidential system is vital for Indonesia to effectively address contemporary governance challenges and maintain national resilience. A well-balanced presidential authority within a democratic framework serves as a foundational element for political stability and effective governance in the modern era. Contribution: This study enhances scholarly understanding of presidentialism within Indonesia's constitutional context, offering analytical insights into how institutional design influences governance outcomes. Additionally, it contributes to constitutional theory by examining presidential power within frameworks of democratic consolidation. Limitations and Suggestions: The study is limited by a lack of empirical data regarding governance outcomes across different presidential administrations. Future research could benefit from comparative analyses of presidential systems in similar emerging democracies, as well as longitudinal studies on presidential effectiveness in specific policy areas